Exploring the Linkages between Gender-specific Human Capital, Foreign Direct Investment and Economic Growth: Evidence from Pakistan - Shaheen, Sania; Hussain, Babar; Ameer, Nadia (Journal of Quantitative Methods, 2021)
This study empirically examined the combined interaction of human capital and foreign direct investment on the economic growth of Pakistan as well as long and short term impact of foreign direct investment and human capital on the economic growth of Pakistan. For achieving the study objectives candidate variables annual time series data of thirty nine years (1976-2014) were collected from the various publications of economic surveys, state bank of Pakistan (SBP) and world development indicator (WDI). To examines the long-term impacts, autoregressive distributed lag (ARDL) econometric techniques were employed, and to estimate the short tun association among variables vector error correction model (VECM) were used to find the study results. The study findings concluded that the interactive term human capital and foreign direct investment has a direct and significant contribution in encouraging economic growth of Pakistan. Moreover, results reveal that in the short run, gender-neutral interactive human capital and foreign direct investment have a significant and direct linkage with economic growth. However, in gender-specific human capital, male human capital and female human capital have an inverse association with economic growth perhaps because of the fact that lack of opportunities and underutilization of labor force in the short run. The outcomes of the study suggests that government should give its attention to promote more human development strategies that provide educated and highly qualified people. The productive utilization of this qualified and skilled human capital in those sectors where most foreign direct investment, along with modern technologies also stimulates economic growth. This, in turn, attracts more quality FDI for Pakistan for sustainable development.